Are winter and breeding bird communities able to track rapid climate change? Lessons from the high North. Issue 3 (17th January 2017) - Santangeli, Andrea; Lehikoinen, Aleksi
Abstract: Aim: Climate change is a major threat to biodiversity and a major factor underlying observed shifts in species distribution, abundance and phenology. Research effort on climate change impacts on species has often been based on single‐species studies focused on a single season, typically the breeding season, of species life cycles. We test how well winter and breeding bird communities are able to track climate change. Location: Finland. Methods: We use a dataset consisting of bird counts from the winter and the breeding period spanning over four decades and a 1000 km latitudinal gradient across Finland, Northern Europe. We use the bird count data in combination with a species‐specific average temperature index to derive a functional index, the Community Temperature Index (CTI), which provides a measure of the relative temperature average of a community. Results: We show that the CTI of the winter bird community (CTIw ) in Finland has increased significantly over the past four decades, but not as fast as the average winter temperature. Across Finland, CTIw decreased towards the north and the east of the country and increased with increasing temperature. Further, we show that change in CTI through time (from 1970s–1980s to 2000–2014) was similar between the winter and the breeding communities. Main conclusions: Overall, our results suggest that while the winter and breeding bird communities are, to a certain level, tracking increasing temperatures, the magnitude of temperature change is multiple times greater than the magnitude of community shifts. This is particularly true for the winter birds that are facing the most rapid temperature shifts. Our findings shed light on the importance of assessing and eventually addressing the effects of rapid climate warming beyond the breeding season of species life cycles.